Q: What is negative -k plus negative -k if k equals 2?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

If: y = kx -2 and y = x^2 -8x+7 Then the values of k work out as -2 and -14 Note that the line makes contact with the curve in a positive direction or a negative direction depending on what value is used for k.

Using the discriminant of b^2 -4ac = 0 the value of k works out as -2

Equation: x^2 +2kx +10x +k^2 +5 = 0 Using the discriminant: (2k +10)^2 -4*1*(k^2 +5) = 0 Multiplying out the brackets: 4k^2 +40K +100 -4k^2 -20 = 0 Collecting like terms: 40k +80 = 0 => 40k = -80 => k = -80/40 Therefore the value of k = -2

==> 3k+14=k ==>3k-k=-14 ==>2k=-14 ==>k=-7 ans...

Find the remainder when f(x) is divided by (x - k) ƒ(x) = 2x3 + 3x2 + 4x + 18; k = -2 (x - k) = (x - (-2)) = (x + 2) x + 2 = 0 x = -2 By Remainder Theorem ƒ(x) = 2x3 + 3x2 + 4x + 18 ƒ(-2) = 2(-2)3 + 3(-2)2 +4(-2) + 18 = 2(-8) + 3(4) + 4(-2) +18 = -16 + 12 -8 +18 = 6 Thus, the remainder is 6

Related questions

k = -1

50

3k-1=k+2 2k=3 k=3/2=1.5

The answer to negative 6 over 5K equals 12 is k equals -10.

j=-3 and k=2

5k + 2 = -2 Therefore, 5k = -4 k = -4/5 k = -0.8

k = 2 7 + (5 x 2) = 17 (8 x 2) + 1 = 17

They are +/- 5*sqrt(2)

Equation: x^2 +2kx +10x +k^2 +5 = 0 Using the discriminant: (2k +10)^2 -4*1*(k^2 +5) = 0 Solving the discriminant: k = -2

If: y = kx -2 and y = x^2 -8x+7 Then the values of k work out as -2 and -14 Note that the line makes contact with the curve in a positive direction or a negative direction depending on what value is used for k.

Yes, they are exactly the same, both of them increment k in 1.

Using the discriminant of b^2 -4ac = 0 the value of k works out as -2